The Little Data Book on Private Sector Development 2012 - World Bank (Washington, DC, 2013)
Access to reliable cross-country data on private sector development is crucial when formulating responses to economic crises. When downturns affect exports, investment, and growth negatively, making life easier for business is a significant step towards economic recovery. This has become obvious during the global financial crisis as governments have tried to stimulate economic growth through the creation of more robust private and finance markets. Improving the investment climate facilitates economic adjustment as it helps attract capital to create jobs and provide basic services. Unsurprisingly, the availability of cross-country data on the business environment has rapidly expanded in recent years; including data from the World Bank Group's doing business project, enterprise surveys, and the entrepreneurship snapshots. The data sources presented in this book report on the scope and types of regulations that enhance and constrain business activity and provide information on business owners' assessment of the business environment. The data have led to new research, enabled benchmarking, and informed the reform process in many developing countries. Included in this guide are indicators on the economic and social context, the investment climate, private sector investment, finance and banking, and infrastructure. Though a pocket guide cannot include all relevant variables, the indicators that are included provide users with a general understanding of the private sector in each country.